ChemInform Abstract: Cyclometalated Iridium Complexes for Transfer Hydrogenation of Carbonyl Groups in Water. Issue 27 (13th June 2013) - Wei, Yawen; Xue, Dong; Lei, Qian; Wang, Chao; Xiao, Jianliang
Abstract A new protocol for the reduction of ketones and aldehydes in acidic aqueous conditions using formic acid as the hydrogen source and cyclometalated iridium complexes as catalysts is described.